Morphological adaptation of loan words : a case of noun Gallicisms in Slovak - Daniel Vojtek (Études romanes de Brno)
The linguistic contact between Slovak and French gave birth to more than 3,000 loan, simple and complex words. Of the 748 simple words, nouns account for a major proportion of 642 lexemes. The present study typologizes, systematizes and analyses the process of their morphological adaptation, preceded by more or less significant change of pronunciation, orthography and grammatical gender assignment, in the transition from a predominantly analytic language (French) to a flectional language (Slovak). In certain cases, the inflectional formants of noun Gallicisms in Slovak carry the French derivational formants, they are characterized by a certain degree of polyfunctionality and require a more detailed qualitative and quantitative analysis which shows that, occasionally, in the case of French derivatives, the Slovak Gallicisms carry over even the morphological (sometimes also onomasiological) structure from Latin.